2021
DOI: 10.3390/rs13214452
|View full text |Cite
|
Sign up to set email alerts
|

Shallow-Water Benthic Habitat Mapping Using Drone with Object Based Image Analyses

Abstract: Spatial information on benthic habitats in Wangiwangi island waters, Wakatobi District, Indonesia was very limited in recent years. However, this area is one of the marine tourism destinations and one of the Indonesia’s triangle coral reef regions with a very complex coral reef ecosystem. The drone technology that has rapidly developed in this decade, can be used to map benthic habitats in this area. This study aimed to map shallow-water benthic habitats using drone technology in the region of Wangiwangi islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 76 publications
1
17
1
2
Order By: Relevance
“…Wahidin et al (2015), using Landsat 8 OLI images with support vector machine (SVM), random tree (RT), bayyesian, k-nearest neighbor (KNN) and decision tree (DT) shows that the algorithm SVM has a better ability than other algorithms with an overall accuracy rate of 73% with seven classes. Nababan et al (2021), using drone imagery and applying the SVM algorithm, resulted in an overall accuracy of 77.4 % in 12 classes and 81.1% in 9 classes. The Z test is used to determine whether two or more image classifications differ significantly or not (Congalton and Green 2009).…”
Section: Test Accuracymentioning
confidence: 99%
“…Wahidin et al (2015), using Landsat 8 OLI images with support vector machine (SVM), random tree (RT), bayyesian, k-nearest neighbor (KNN) and decision tree (DT) shows that the algorithm SVM has a better ability than other algorithms with an overall accuracy rate of 73% with seven classes. Nababan et al (2021), using drone imagery and applying the SVM algorithm, resulted in an overall accuracy of 77.4 % in 12 classes and 81.1% in 9 classes. The Z test is used to determine whether two or more image classifications differ significantly or not (Congalton and Green 2009).…”
Section: Test Accuracymentioning
confidence: 99%
“…The decrease in cost, development of more advanced technologies, such as higher resolution and more lightweight cameras, plus availability of consumer-level drones (i.e. UAVs, uncrewed aerial vehicles) has driven their widespread adoption as a research and teaching tool across the geosciences (Jordan 2015, Behrman et al 2019, Dering et al 2019, Samsu et al 2019, Cirillo 2020 and other disciplines such as ecology (Charton et al 2021, Nababan et al 2021, archeology (Hendrickx et al 2011), and forensic science (Stanković et al 2021). The ability for geoscience researchers and educators to integrate aerially obtained data into their analyses is proving highly valuable both in the field for locating suitable study areas, and also post-fieldwork with numerous use cases reported (Ryberg et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Generalmente se utilizan imágenes de satélite de alta resolución espacial y espectral en costas someras para obtener clasificación de unidades mediante procesamiento digital de estas imágenes (Silvero et al 2021). También se ha empleado imágenes obtenidas a partir de vehículos aéreos y submarinos no tripulados (drones) para la observación indirecta de hábitats bentónicos (Tait et al, 2021;Nababan et al, 2021) Del Pino-Machado et al…”
Section: Introductionunclassified